2017
DOI: 10.24215/15142590e005
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalencia de infección por el virus de leucosis bovina durante 2015 en rodeos de cría de la Zona Deprimida del Río Salado, provincia de Buenos Aires, Argentina

Abstract: Leucosis bovina en la cuenca del saladoResumen: La leucosis enzoótica bovina (LEB) es una enfermedad crónica, linfoproliferativa y altamente contagiosa producida por el virus de la leucosis bovina (VLB). La sangre es una fuente importante de infección, principalmente en la práctica veterinaria, considerando que solo 5 microlitros son suficientes para infectar a un bovino en forma experimental. La Zona Deprimida del Río Salado (ZDRS) está formada por poco más de 6 millones de hectáreas con una cantidad de terne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…In cattle, the polyclonal expansion of B cells, which is characteristic of animals with persistent lymphocytosis, occurs almost exclusively within the CD5+ IgM+ B cell subset ( 4 , 5 ) and these B cells are also the primary target for BLV proviral integration ( 5 , 6 ). However, other cell types like CD4 + T cells, CD8 + T cells, γ/δ T cells, monocytes and granulocytes can also be infected by BLV ( 3 , 7 10 ). The free virus is rarely detected in vivo , and it is believed that it appears only during the acute stage of infection, before the development of neutralizing antibodies ( 11 ).…”
Section: Enzootic Bovine Leukosismentioning
confidence: 99%
“…In cattle, the polyclonal expansion of B cells, which is characteristic of animals with persistent lymphocytosis, occurs almost exclusively within the CD5+ IgM+ B cell subset ( 4 , 5 ) and these B cells are also the primary target for BLV proviral integration ( 5 , 6 ). However, other cell types like CD4 + T cells, CD8 + T cells, γ/δ T cells, monocytes and granulocytes can also be infected by BLV ( 3 , 7 10 ). The free virus is rarely detected in vivo , and it is believed that it appears only during the acute stage of infection, before the development of neutralizing antibodies ( 11 ).…”
Section: Enzootic Bovine Leukosismentioning
confidence: 99%
“…Despite this, there are different investigations on EBL worldwide. Seroprevalences of 0.36% have been reported in the Zona Deprimida del Río Salado (Buenos Aires, Argentina) ( Panei et al , 2017 ), 2.27% in three provinces of Ecuador ( Vásconez-Hernández et al , 2017 ), 10.8% in Paraíba (Brazil) ( Ramalho et al , 2021 ), 10% in China ( Ma et al , 2021 ), and 17.7% in Egypt ( Selim et al , 2020 ), with seropositivity below those found in the municipalities evaluated in the present study, except in Ubaté with a seroprevalence lower in contrast to Selim et al (2020) .…”
Section: Discussionmentioning
confidence: 99%